11 steps to awesome with Kubernetes, Istio, and Knative : LiveLessons (LiveLessons (Indianapolis, Ind.), 2020)
"Kubernetes from the Cloud Native Computing Foundation is the defacto standard for hybrid cloud containerized application orchestration-from an on-premises data center to all major public cloud providers. While Docker is a tool for building, distributing, and running Linux containers, Kubernetes is a Linux container orchestration system that is more extensive than Docker Swarm and is meant to coordinate massive clusters of compute nodes and simplify your application deployment into production. Burr Sutter, Red Hat's Global Director of Developer Experience, offers detailed tips and techniques for leveraging Kubernetes, Istio, and Knative as part of your next application architecture, be it traditional monolithic, microservices, or serverless. Kubernetes is the hybrid and multi-cloud deployment platform for applications and application developers. Get practical, hands-on guidance to get you started and keep you growing, from novice to architect in 11 lessons."--Resource description page